2008
DOI: 10.1115/1.2953235
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations on Microcoining of Stainless Steel 304

Abstract: Increasing demands for miniature metallic parts have driven the application of microforming in various industries. Only a limited amount of research is, however, available on the forming of miniature features in high strength materials. This study investigated the forming of microfeatures in Type 304 stainless steel by using the coining process. Experimental work was performed to study the effects of workpiece thickness, preform shape, grain size, and feature size on the formation of features ranging from 320μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…In general, unfilling could occur in creating protrusion, while a close contact between blank and tooling can usually be attained in forming cavity by indentation [16]. Kim et al [74,75] conducted the experiment of forming micro-sized protrusions on the blank surface through microcoining process using stainless steel 304 and pure copper, as shown in Fig. 4.35a.…”
Section: Microcoiningmentioning
confidence: 98%
“…In general, unfilling could occur in creating protrusion, while a close contact between blank and tooling can usually be attained in forming cavity by indentation [16]. Kim et al [74,75] conducted the experiment of forming micro-sized protrusions on the blank surface through microcoining process using stainless steel 304 and pure copper, as shown in Fig. 4.35a.…”
Section: Microcoiningmentioning
confidence: 98%
“…By incorporating the expanded Hall-Petch expression from [20] and [30] into Eq. (4), the next formulation for forging force is obtained, in which the forging force depends on true strain and the crystalline grain size:…”
Section: Extended Empirical Model Depending On the Crystalline Grain mentioning
confidence: 99%
“…K hp is interpreted as the resistance of the grain boundary to deformation (parameter from a HallPetch model), and d is the size of the crystalline grain. Parameters α SE and β SE are determined on the basis of the findings of [20] and [30]. The size factor (λ) is obtained from the diagram on Fig.…”
Section: Extended Empirical Model Depending On the Crystalline Grain mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the flow curve increases when the ratio further decreases from 191 to 49 in hydraulic bulge test. Kim et al (2008) developed a flow stress model, which considers the grain and feature size effect to examine the forming behaviour in the coining process. The results revealed that the forming depth is affected by the specimen thickness, grain size and feature size.…”
Section: Introductionmentioning
confidence: 99%